Perancangan dan Analisis Antena Dipole Pada Frekuensi 2,4 GHz Untuk Modul Xbee S2 Pro Menggunakan HFFS 14.0 - Shinta Romadhona; Diana Alia; Maya Zulfida (Aviation Electronics, Information Technology, Telecommunications, Electricals, Controls (AVITEC), 2020)
Xbee s2 pro module works at 2,4 Ghz using IEEE 802.15.4 standard and polarization are linear. There are many types of antennas that can be used, which one is the dipole antenna. The simulation model implemented in this study uses Ansoft HFSS 14.0 software. HFSS stands for high frequency structure simulator is a pioneer in the use of finite element method for electromagnetic wave simulators that implement tangential vector finite elements, adaptive meshing and Adaptive Lanczos-Pade Sweep (ALPS) technology. By using HFSS 14.0 simulation, the axial ratio value of 35.0359 dB that means linier polarization. For the value of s-parameter -21,1851 db and VSWR value approaches 1, that is 1.5195 db. The gain value obtained is 0.7469 dB, the gain value needs to be optimized by using a metamaterial to get a good gain.